The Screening and Isolation of Ethyl-Carbamate-Degrading Strains from Fermented Grains and Their Application in the Degradation of Ethyl Carbamate in Chinese Baijiu - Siyu Xue; Naihui Dong; Kexin Xiong; Hui Guo; Yiwei Dai; Huipeng Liang; Yingxi Chen; Xinping Lin; Beiwei Zhu; Sufang Zhang (Foods, 2023)
Ethyl carbamate (EC), a 2A carcinogen produced during the fermentation of foods and beverages, primarily occurs in distilled spirits. Currently, most studies focus on strategies for EC mitigation. In the present research, we aimed to screen strains that can degrade EC directly. Here, we report two Candida ethanolica strains (J1 and J116), isolated from fermented grains, which can reduce EC concentrations directly. These two yeasts were grown using EC as the sole carbon source, and they grew well on different carbon sources. Notably, after immobilization with chitosan, the two strains degraded EC in Chinese Baijiu by 42.27% and 27.91% in 24 h (from 253.03 ± 9.89 to 146.07 ± 1.67 and 182.42 ± 5.05 μg/L, respectively), which was better than the performance of the non-immobilized strains. Furthermore, the volatile organic compound content, investigated using gas chromatography-mass spectrometry, did not affect the main flavor substances in Chinese Baijiu. Thus, the yeasts J1 and J116 may be potentially used for the treatment and commercialization of Chinese Baijiu.